2023
DOI: 10.1002/adhm.202300163
|View full text |Cite
|
Sign up to set email alerts
|

MnO2 Coated Mesoporous PdPt Nanoprobes for Scavenging Reactive Oxygen Species and Solving Acetaminophen‐Induced Liver Injury

Abstract: As one of the most widely used drugs, acetaminophen, is the leading cause of acute liver injury. In addition, acetaminophen‐induced liver injury (AILI) has a strong relationship with the overproduced reactive oxygen species, which can be effectively eliminated by nanozymes. To address these challenges, mesoporous PdPt@MnO2 nanoprobes (PPM NPs) mimicking peroxide, catalase, and superoxide dismutase‐like properties are synthesized. They demonstrate nontoxicity, high colloidal stability, and exceptional reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“… 103 Lu et al reported a MnO 2 -coated mesoporous PdPt alloy nanozyme with enhanced ROS-scavenging ability for the amelioration of APAP-induced ALI. 104 With the rapid progress of nanotechnology, nanomedicines with self-propulsion capability have garnered increasing attention due to their active drug delivery and deeper penetration ability. 105 However, most currently available ROS-scavenging nanozymes cannot actively eliminate ROS because they passively diffuse rather than self-charged propulsion.…”
Section: Ros-scavenging Nanozymes For Ali Alleviationmentioning
confidence: 99%
“… 103 Lu et al reported a MnO 2 -coated mesoporous PdPt alloy nanozyme with enhanced ROS-scavenging ability for the amelioration of APAP-induced ALI. 104 With the rapid progress of nanotechnology, nanomedicines with self-propulsion capability have garnered increasing attention due to their active drug delivery and deeper penetration ability. 105 However, most currently available ROS-scavenging nanozymes cannot actively eliminate ROS because they passively diffuse rather than self-charged propulsion.…”
Section: Ros-scavenging Nanozymes For Ali Alleviationmentioning
confidence: 99%
“…15 Besides rapid sensing of APAP, various techniques are developed for the treatment of APAP-caused accidents. 16–18…”
Section: Introductionmentioning
confidence: 99%